Gastrin promotes angiogenesis by activating HIF-1α/β-catenin/VEGF signaling in gastric cancer - Tang, E.; Wang, Yongfeng; Liu, Tiemei; Yan, Bin (Gene, 2019)
Angiogenesis is recognized as a sign of cancer and facilitates cancer progression and metastasis. Suppression of angiogenesis is a desirable strategy for gastric cancer (GC) management. In this study, we showed a novel role of gastrin in angiogenesis of GC. We observed that treatment with gastrin 17 (G17) increased the proliferation of AGS cells and enhanced tube formation during normoxia and hypoxia. The expression level of VEGF were increased by G17 treatment as well. Experiments on the mechanism showed that G17 promoted HIF-1α expression, which subsequently enhanced β-catenin nuclear localization and activation of TCF3 and LEF1 and finally resulted in angiogenesis by upregulating VEGF. An in vivo experiment confirmed that G17 enhanced GC cell proliferation and angiogenesis in the resultant tumor. In conclusion, our findings indicate that gastrin promotes angiogenesis via activating HIF-1α/β-catenin/VEGF axis in GC. •Gastrin promotes proliferation of GC cells and angiogenesis under normoxic and hypoxic conditions.•Gastrin promotes angiogenesis through the β-catenin/VEGF pathway in the normoxic condition.•Gastrin promotes angiogenesis via the HIF-1α/β-catenin/VEGF pathway under hypoxia.•Gastrin promotes GC cell proliferation and angiogenesis during hypoxia in vivo.